A klímaváltozás és a demográfiai folyamatok kapcsolata Magyarországon - járási szintű előrejelzések 2051-ig - Uzzoli, Annamária; Tagai, Gergely; Király, Gábor; Czirfusz, Márton; Koós, Bálint (Közép-Európai Közlemények, 2016)
The article is based on the most important results and experiences of a national research project (EEA-C12-11). The priority of this project is that it delivers spatially disaggregated data on future demographic trends in Hungary through 2051, on the scale of LAU 1. The other special task in the research is to define the effects of climate change on socio-economic processes, especially on demographic features. The study examines the connection between these processes and climate change through heat waves, thereby addressing the needs of those social groups most vulnerable to climate change. The most important outcomes of the research project will facilitate adaptation to climate change and its effects, the provision of a scientific basis for such adaptation, the devising and implementation of measures pertaining to the individual regions, the establishment of strategies and similar pilot projects at a regional level and the improvement of the skills and abilities of the experts and policy makers concerned and of the climate awareness of society and local communities.